2014
DOI: 10.1002/ejlt.201400014
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry (Rubus fruticosus L.) and raspberry (Rubus idaeus L.) seed oils extracted from dried press pomace after longterm frozen storage of berries can be used as functional food ingredients

Abstract: Prolonged storage of frozen berries had some impact on the quality of the oils compared to the fresh sample. Free fatty acid content (FFA) and peroxide values (PV) increased in blackberry oil (BO) (from 1.18 to 3.54% oleic acid) and in raspberry oil (RO) (from 2.66 to 8.84% oleic acid). PV values were higher in the RO (increased from 4.82 to 13.97 mmol/kg) than in the BO (increased from 3.73 to 11.14 mmol/kg). Both oils were very high in omega‐6 FA (%): 63.66 ± 0.49 for BO and 54.94 ± 0.18 for RO, and omega‐3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 48 publications
5
41
0
Order By: Relevance
“…It was found that the LA and ALA are the main components of the tested oils. These measurements are comparable to literature [10,15,32]. The FA composition may be slightly different due to the fruit origin, but despite this, a high PUFA content remained in all cases.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that the LA and ALA are the main components of the tested oils. These measurements are comparable to literature [10,15,32]. The FA composition may be slightly different due to the fruit origin, but despite this, a high PUFA content remained in all cases.…”
Section: Resultssupporting
confidence: 89%
“…Polyphenols have potentially beneficial effects on health including antiviral, antimicrobial, and antioxidant activity. These properties are usually due to tocopherols, phytosterols and phenolics [15]. Most of the fruit originate from China, and the oils are extracted with solvents or by supercritical CO 2 .…”
Section: Fruit Seed Oilsmentioning
confidence: 99%
“…The RO used in this study was especially rich in linoleic and a-linolenic acids (18:3n23; 50.7% and 29.2%, respectively), which is similar to the results obtained by other authors who determined the FA profile of RO (6,10,26). However, in the aforementioned studies, the contents of linoleic and a-linolenic acid were higher by up to 4% and 5.5%, respectively, which can be a consequence of the different growth conditions of raspberries or the extraction method that was applied.…”
Section: Discussionsupporting
confidence: 90%
“…Stigmasterol and campesterol were also detected but in much smaller quantities, 70–119 mg 100 g −1 and 50–80 mg 100 g −1 extract, respectively. These sterols, which also constituted the main sterol fraction, had been identified previously, using a GC‐MS method (Table ) . Blackberry cultivated in Poland seems to be the richest source of sterols; the amount is more than two times higher than in plants cultivated in Serbia …”
Section: Resultsmentioning
confidence: 99%